A jornada de Lope de Aguirre: evento, personagem, história - Schell, Deise Cristina (Universidade do Vale do Rio dos Sinos, 2011)
This dissertation researches how written records were produced regarding the history of a character and an event during the Spanish Conquest of the Americas. It is about the Journey of Omagua and Dorado [1560-1561], an expedition which traveled to unknown lands in America - in this case, the Amazon rainforest - searching for treasures and wealth. The Journey is known for the travelers' rebellious actions as well as for Lope de Aguirre, main character of the quest. We have tried to identify how this event and this character were represented and interpreted in diferent times in History through written records produced by many authors - from the conquerors, who were part of the expedition to historians from the 20th century. We intend to verify how the historiography on the Journey was built and, furthermore, how the memory of the event was established. Analyzing how the Journey's history was written will help us evaluate our work as historians by leading us to a reflection on historic knowledge produced through time.
Keywords: História; Jornada de Omagua y Dorado; Lope de Aguirre; Conquista da América; History; Journey of Omagua and Dorado; Lope de Aguirre; Conquest of the Americas; ACCNPQ::Ciências Humanas::História